C-Terminal Farnesylation of UCH-L1 Plays a Role in Transport of Epstein-Barr Virus Primary Oncoprotein LMP1 to Exosomes - E. Kobayashi (American Society for Microbiology, 2018)
ABSTRACT Increasing evidence shows that exosomes are key regulators in cancer cell-to-cell communication. Several reports on Epstein-Barr virus (EBV)-related malignancies demonstrate that latent membrane protein 1 (LMP1) secreted by exosomes derived from EBV- or LMP1-positive cells can promote cancer progression and metastasis. However, the mechanism by which LMP1 is loaded into exosomes is still poorly understood. Here, we examined whether the process of LMP1 loading into exosomes is linked to the multifunctional molecule of the ubiquitin system—ubiquitin C-terminal hydrolase-L1 (UCH-L1). For the first time, we demonstrate that LMP1 is physically associated with UCH-L1 and that directing of LMP1 to exosomes is mediated by C-terminal farnesylation of UCH-L1. Additionally, we found that the FTI-277 farnesyltransferase inhibitor reduces motility- and anchorage-independent growth of EBV-positive cells in functional assays. On the basis of our results, we conclude that C-terminal farnesylation of UCH-L1 is one of the key mechanisms by which LMP1 is sorted to exosomes. We hypothesize that inhibition of farnesylation with specific small-molecule inhibitors blocks exosome-mediated transfer of prometastatic molecules such as LMP1 during cancer cell-to-cell communications and thereby impedes the process of cancer invasion. IMPORTANCE Exosomes are small vesicles that cells secrete into the extracellular space, and there is increasing evidence that they have pivotal roles in cell-to-cell communication in malignancy. It is reported also that EBV-associated malignant cells, including those derived from nasopharyngeal carcinoma (NPC) and B-cell lymphoma, secrete exosomes. These EBV-related exosomes may contain viral products such as latent membrane protein 1 (LMP1) and may contribute to cancer progression. The aim of this study was to investigate the mechanism by which those viral products are loaded in exosomes. In this study, we show for the first time that ubiquitin C-terminal hydrolase-L1 (UCH-L1) and its C-terminal farnesylation, a posttranslational lipid modification, contribute to this mechanism. Our results also suggest that inhibition of UCH-L1 farnesylation is a potential therapeutic target against cancer metastasis and invasion.